P159 Low rate vascular access related infections in thechronic haemodialysis patient cohort in a tertiary paediatric hospital. (June 2019) - Raftery, Maria; Raftery, Tara; Flynn, Joan; Murray, Karina; Sweeney, Clodagh; Lewis, Malcolm; Stack, Maria; Riordan, Michael; Dolan, Niamh; Awan, Atif
Abstract : Background: Vascular access is required for haemodialysis (HD), a form of renal replacement therapy required when a child has acute or end stage kidney disease (ESKD). Central venous catheter (CVC) line infections are the second most common cause of vascular access loss in the long term HD patient, commonly caused by poor hand hygiene practices, clinical environment or inadequate sterilisation procedures. In the literature the reported rates of infection range from 0.8–4.8 episodes/1000 catheter days in this patient group. Aim: To audit CVC line related infection rates in our tertiary HD unit in Temple Street Children's University Hospital (TSCUH) over a 5 year period. Methods: A retrospective review was carried out on all patients who had HD from January 2012- January 2017 (inclusive) using a CVC. Results/Findings: 34 patients required HD, of which 44% were female and 56% male. Twenty-three patients (68%) were aged between 5–10 years of age. Dysplastic kidneys was the most common reason for requiring HD (n=9, 26.2%). Eight patients required HD for 1–6 months, 5 patients for 6–12 months, 19 patients for 12–48 months, and 2 patients for >60 months. Five out of 34 children developed CVC line infections with an overall infection rate of 0.22 episodes per 1000 catheter days. Loss of protective caps was the main reason for infection (n=3). Staph-aureous, pseudomonas oryzihabitans, enterococcus faecalis and mixed coagulase negative staphylococci were the identified organisms causing infection. Conclusions: CVC line infections in long-term HD patients attending TSCUH are maintained at a low rate in comparison to published data. Strict application of Aseptic Non Touch Technique shows favourable results without the need for prophylactic antibiotics locks. Future work includes a cost benefit analysis of this practice.